A Study on Clean Water Quality in Taman Pagoh Jaya - Sahmat, Nur Awine Aina; Rosli, Mohd Arif; Abdul Rahman, Mohd Fahmi (Progress in Engineering Application and Technology, 2023)
Water is one of the most basic requirements for survival. Therefore, this study aims to assess the quality of cold water system, which has an impact on the supply of direct and indirect clean water in the study area. The objective of this research is to determine the physicochemical parameters of water quality at Taman Pagoh Jaya. Then the results obtained were compared with direct and indirect water supply and the data was verified based on the standard method Malaysian Drinking Water Quality Standard (MDWQS). The implementation method was carried out through sample analysis in 4 sampling stations which are Taman Pagoh Jaya 3/11 (S1), Taman Pagoh Jaya 2/13 (S2) for direct system and Taman Pagoh Jaya 3/11 (S3), Taman Pagoh Jaya 3/4 (S4) for indirect system. The parameters that were analysed to determine the physicochemical parameters are pH, temperature, DO, TSS and COD, which were measured based on the standard method Malaysian Drinking Water Quality Standard (MDWQS). For pH, temperature, DO, TSS and COD the range for each parameter are between pH 7.35 to 7.64, 26.2 ˚C to 27.4˚C, 6.04 mg/L to 6.74 mg/L, 13 mg/L to 24 mg/L and 3 mg/L to 6 mg/L respectively. Based on the results, the parameters of pH, temperature, TSS, and COD are not exceeded, indicating that tap water for all four sampling stations is safe to use, while DO indicated that the water quality of all sampling stations required conventional treatment. It is also recommended to continue more sampling stations and physicochemical parameters at Taman Pagoh Jaya in the future.